2010
DOI: 10.5194/angeo-28-1741-2010
|View full text |Cite
|
Sign up to set email alerts
|

Features of the F3 layer occurrence over the equatorial location of Trivandrum

Abstract: Abstract. The general features of the F3 layer occurrence over the magnetic equatorial location of Trivandrum (8.5 • N; 77 • E; dip lat ∼ 0.5 • N) in India during the period from 1996-2005 are presented using the ionosonde observations. The study brings out that the F3 layer occurrence over Trivandrum is weak and rare compared to the other equatorial locations. The F3 layer occurrence is relatively more pronounced during the magnetically active conditions, thus indicating the dependence of the layer formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 27 publications
4
25
0
Order By: Relevance
“…Raghavarao and Sivaramam [67] concluded that the topside ledges occurred more frequently and lasted longer into the night during sunspot minimum period than at sunspot maximum. The same conclusion was made regarding the appearance of F3 layer according to ground-based sounding data [43].…”
Section: Latitudinal Dependence Of the F3 Layermentioning
confidence: 56%
See 3 more Smart Citations
“…Raghavarao and Sivaramam [67] concluded that the topside ledges occurred more frequently and lasted longer into the night during sunspot minimum period than at sunspot maximum. The same conclusion was made regarding the appearance of F3 layer according to ground-based sounding data [43].…”
Section: Latitudinal Dependence Of the F3 Layermentioning
confidence: 56%
“…Similarly, according to the ground-based data F3 layer is observed rarely at the equator than at low latitudes ±(7∼8 • ) [37,39,41,65]. Recent studies show that the F3 layer near the magnetic equator behaves in a different way than that in the magnetic low-latitude region [41,43,66]. The F3 layer moves rapidly upward near the magnetic equator, while it stays almost at a certain altitude in the magnetic low-latitude region.…”
Section: Latitudinal Dependence Of the F3 Layermentioning
confidence: 99%
See 2 more Smart Citations
“…This additional layer was later renamed the F 3 layer because it has the same chemical composition as the F region . After that, the subject of the F 3 layer received extensive investigations at low and equatorial latitudes concerning its spatial and temporal distribution [Jenkins et al, 1997;Balan et al, 1998;Hsiao et al, 2001;Batista et al, 2002;Rama Rao et al, 2005;Zain et al, 2008;Uemoto et al, 2007;Sreeja et al, 2010;Zhao et al, 2011], and also its storm time characteristics [Zhao et al, 2005;Paznukhov et al, 2007;Balan et al, 2008;Sreeja et al, 2009;Zong et al, 2010]. The mechanism of the storm time F 3 layer resembles that in quiet periods and was caused by a rapid upward E × B drift resulting from an eastward penetration electric field but sometimes can be caused by strong field-aligned diffusion due to the storm time meridional wind surges as proposed by Lin et al [2009aLin et al [ , 2009b.…”
Section: Introductionmentioning
confidence: 99%